The Study of Subjective Assessment of the Safety and Efficacy of Antihypertensive Drugs from the Group of Beta-Blockers and Calcium Antagonists - Tetiana Nehoda (Journal of Global Pharma Technology, 2020)
Introduction: In order to study in more detail the subjective assessment of the effectiveness of antihypertensive monotherapy, the questionnaires of patients were structured. They were divided into groups according to the drugs used by patients belonging to a particular clinical and pharmacological group: beta-blockers and calcium antagonists. The purpose of this study was to study of subjective factual and prognostic assessment of patients' effectiveness of treatment. Materials and methods: Methods such as: questionnaires of patients (content analysis of case histories) were used. Data processing was performed using statistical and mathematical methods and graphical analysis. Results and discussion: There were some patterns of lowering blood pressure in patients on the background of monotherapy of hypertension and patients following the doctor's instructions for treatment. Conclusions: As a result of the study, it was found that most patients follow the recommendations of doctors on the appointment of antihypertensive drugs.